Identification, characterisation and functional analyses of novel beta-catenin associated protein, FLYWCH1 - Muhammad, Belal Abdul-Rahman (2013)
The growing knowledge of cell biology and evidence for the role of β-catenin signalling network in homeostasis and carcinogenesis encourages further investigation into the regulatory network of nuclear β-catenin signalling complex. While the role of canonical Wnt signalling in the development of both normal tissue and malignant tumours is well documented, the molecular basis of these functionally distinct nuclear transcriptional programs is poorly understood. Many proteins are associated with cytoplasmic β-catenin for regulation of Wnt/β-catenin pathway activities. However, in the nucleus, the LEF/TCF family of transcription factors, which have DNA binding properties, remains the sole focus as unambiguous partners of β-catenin.